2023
DOI: 10.3847/1538-4357/acdeeb
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Elemental Abundances in Hot Active Region Cores from Chandrayaan-2 XSM Observations

Biswajit Mondal,
Santosh V. Vadawale,
Giulio Del Zanna
et al.

Abstract: The first ionization potential (FIP) bias, whereby elemental abundances for low-FIP elements in different coronal structures vary from their photospheric values and may also vary with time, has been widely studied. In order to study the temporal variation and understand the physical mechanisms giving rise to the FIP bias, we have investigated the hot cores of three active regions (ARs) using disk-integrated soft X-ray spectroscopic observations with the Solar X-ray Monitor on board Chandrayaan-2. Observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…In an AR, the abundances can also vary with time, depending on the strength of heating and amount of fractionation by wave fluxes. Mondal et al (2023) examined time variation of Al, Mg, Si, and S in three ARs, finding abundance factors no lower than 2 (slightly enhanced over photospheric). Comparing the simulations here, that suggests that there may be an upper limit to nanoflare heating in those ARs of ≈0.1 erg s −1 cm −3 since the abundances never reached photospheric values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an AR, the abundances can also vary with time, depending on the strength of heating and amount of fractionation by wave fluxes. Mondal et al (2023) examined time variation of Al, Mg, Si, and S in three ARs, finding abundance factors no lower than 2 (slightly enhanced over photospheric). Comparing the simulations here, that suggests that there may be an upper limit to nanoflare heating in those ARs of ≈0.1 erg s −1 cm −3 since the abundances never reached photospheric values.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent X-ray observations of flares, however, clearly show that elemental abundances are not fixed and vary with time over the duration of the flare (Del Zanna et al 2021;Mondal et al 2021;Mithun et al 2022;Kepa et al 2023;Nama et al 2023;Rao et al 2023;Suarez & Moore 2023;Woods et al 2023). Similar observations have also found that the abundances of active regions (ARs) vary relatively quickly as well (Mondal et al 2023).…”
Section: Introductionmentioning
confidence: 89%